(untitled) (Revista Innova Educación, 2023)
Gamification is the use of game elements to promote motivation, increase participation, and enhance the teaching and learning process. The purpose of this study was to develop a methodological strategy based on gamification to reinforce the teaching and learning process of the English language at the upper basic level of the Charapotó Educational Unit. A methodology with a socio-critical approach, a mixed approach, and a descriptive research type with a non-experimental design were used. The population consisted of 3 English teachers and 295 upper basic students. The sample included all the teachers, and through a simple random probability sampling analysis, 167 students from the Charapotó Educational Unit in the province of Manabí, Ecuador, were selected. Techniques such as observation, surveys, interviews, and bibliographic analysis were employed, considering the dimensions of teaching resources, the student’s role, and the teacher’s role. The results showed that some students face difficulties in terms of motivation and attitude towards learning the English language, which affects their performance. Therefore, it is necessary to implement strategies that promote motivation and engagement and provide the necessary support to overcome these difficulties. Theoretical references were established to highlight the importance of gamification. The diagnostic phase facilitated the recognition of weaknesses and shortcomings, which were used to structure gamified activities that will enable the implementation of an active, cooperative, and motivating methodology for the generation of meaningful learning.